1999
DOI: 10.1300/j013v29n03_08
|View full text |Cite
|
Sign up to set email alerts
|

How Health Care Providers Help Battered Women: The Survivor's Perspective

Abstract: This qualitative study aimed to describe, from the perspective of domestic violence survivors, what helped victims in health care encounters improve their situation and thus their health, and how disclosure to and identification by health care providers were related to these helpful experiences. Semi-structured, open-ended interviews were conducted with a purposeful sample of survivors in the San Francisco Bay Area. Data were analyzed using constant comparative techniques and interpretative processes. Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…14 Qualitative reports from women who have escaped abuse indicate that even brief discussions with physicians are therapeutic when conversations are conducted in a concerned, nonjudgmental way. 15 Effective communication with a health care provider has been linked to improved health outcomes in a number of areas. 16,17 For domestic violence, physician-nurse communication skills might also be a key predictor of patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…14 Qualitative reports from women who have escaped abuse indicate that even brief discussions with physicians are therapeutic when conversations are conducted in a concerned, nonjudgmental way. 15 Effective communication with a health care provider has been linked to improved health outcomes in a number of areas. 16,17 For domestic violence, physician-nurse communication skills might also be a key predictor of patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Other work suggests that creating an environment with posters and brochures about DV helps to normalize the issue as well as reassuring patients that the inquiry is part of the routine for everyone. 26,27,46,47 Participants reported both positive and negative responses to the 5 DV questions. This suggests that there may not be a perfect question for face-to-face screening.…”
Section: Discussionmentioning
confidence: 99%
“…The act also establishes an independent nongovernmental group that is seeking stakeholder input for refining a mission devoted to patient-centered outcomes research. 39 Given the broad-based support for screening and addressing IPV and among patients, 18,22 it is highly likely that any stakeholder-informed agenda seeking to improve population-based health will support health care interventions for violence and co-occurring psychosocial risk factors. However, at this point it is not yet clear how the movement toward population-based care and patient-centered outcomes will be operationalized and how the incentives can be ultimately aligned to help hospitals and health systems determine how to deliver better health care in ways that reduce costs and improve the health of communities.…”
Section: Future Directionsmentioning
confidence: 99%
“…14 Substantial barriers were identified that span the spectrum of physicians' knowledge, attitudes, beliefs, and behaviors. [15][16][17][18][19][20] Even system-level interventions with extensive physician education demonstrated marked improvements in screening without an increase in IPV identification. 21 During this time, the movement for the use of evidence to guide clinical practice was also developing.…”
mentioning
confidence: 99%